KONTRIBUSI PENDAPATAN IBU RUMAH TANGGA TERHADAP PENDAPATAN KELUARGA (STUDI KASUS PEMETIK TEH DI DESA AIR SEMPIANG KABUPATEN REJANG LEBONG) - Sumantri, Bambang; Ansori, Budi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The objective of this study was to describe housewives motivation to work as tea gathers, and analyze their income contJibution, and measure a correlation of housewives income with family income. The first and second objectives were analysed using descriptive analysis while the last objective used chi-squares analysis. The study conducted in Air Sempiang, Kepahiang distJict, Bengkulu Province. This research concluded that an economic reason such as increasing family income, having personaf income, fulfilling household needs were the main reason motivating housewifes to work. While social motivation, namely as employing theirwaste time, making a friend and culture motivation is another reason. Housewife has ontJibuted 24,85 % of total family income. The research also found that there was a strong correlation between housewife income and her total family income.